Polarographic Study on Binary and Ternery Complexes of Nd(III) with 2-2-Bipyridyl and Urea† - Sahu, G.P.; Lavale, S.C. (Asian Journal of Chemistry, 2010)
Polarographic measurements have been used to determine the overall formation constant of simple and mixed complexes of Nd(III) with urea and 2,2-bipyridyl at 25 ± 0.1ºC. Polarograms of Nd(III)-urea-bipyridyl system at pH 2.40 ± 0.02 in aqueous medium have been used to study the complexes. The reduction of metal and its binary and ternary complexes is found to be reversible and diffusion controlled. Three mixed ligand species [Nd(Bip)(Ur)]3+, [Nd(Bip)(Ur)2]3+ and [Nd(Bip)2(Ur)]3+ have been found in situ and their stability constants were computed. The values are log B11 = 4.90, log B12 = 5.26 and log B21 = 6.07. The mixing constant Km = B11/ and stabilization constant log Ks = log Km – log 2 are computed; the log values are found to be 1.02 and 0.72 respectively. The positive values of mixing constant and stabilization constant proved that mixed complexes are more stable than simple binary complexes. Disproportion constant for reaction 2[Nd(Bip)(Ur)]3+ ⇌ [Nd(Bip)2]3+ + [Nd(Ur)2]3+ was found to be –1.14, The –ve value clearly indicates preferential tendency of Nd(III) to form mixed complex species.